Psidium guajava L.: From byproduct and use in traditional Mexican medicine to antimicrobial agent - Gutierrez-Montiel, Daniela; Guerrero-Barrera, Alma L.; Chávez-Vela, Norma A.; Avelar-Gonzalez, Francisco J.; Ornelas-García, Ingrid G. (Frontiers in Nutrition, 2023)
Mexico is one of the largest guava producers in the world, so it has access to a huge amount of waste and byproducts obtained after the industrial processing of the fruit. This review discusses the potential recovery of this residue for its application as an antimicrobial agent, considering the phytochemical composition, the bioactivity reported in-vivo and in-vitro, and the toxicology of the plant. Nowadays there is a growing demand for more natural and safer products, so the use of guava extracts is an interesting initiative, especially due to its availability in the country, its wide variety of traditional uses, and its phytochemical profile. This review highlights the importance and potential antimicrobial use of this plant in today's world.